2001
DOI: 10.1128/aem.67.10.4760-4764.2001
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Salmonellae on and in Tomato Plants from the Time of Inoculation at Flowering and Early Stages of Fruit Development through Fruit Ripening

Abstract: The fate of salmonellae applied to tomato plants was investigated. Five Salmonella serotypes were used to inoculate tomato plants before and after fruits set, either by injecting stems with inoculum or brushing flowers with it. Ripe tomato fruits were subjected to microbiological analysis. Peptone wash water, homogenates of stem scar tissues, and homogenates of fruit pulp were serially diluted and plated on bismuth sulfite agar before and after enrichment. Presumptive Salmonella colonies were confirmed by sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
3
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(141 citation statements)
references
References 20 publications
3
128
3
7
Order By: Relevance
“…For example, gfp-tagged strains of S. enterica colonized the interior of tomato plants when grown hydroponically (Guo et al, 2001;Guo et al, 2002) and various S. enterica serovars were able to colonize Medicago sativa and other leguminous plants endophytically and epiphytically (Dong et al, 2003;Wang et al 2006). Also, an avirulent strain of S. enterica serovar Typhimurium colonized carrots and radishes which were grown on a field treated with S. enterica serovar Typhimurium-contaminated composted manure or irrigation water (Islam et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, gfp-tagged strains of S. enterica colonized the interior of tomato plants when grown hydroponically (Guo et al, 2001;Guo et al, 2002) and various S. enterica serovars were able to colonize Medicago sativa and other leguminous plants endophytically and epiphytically (Dong et al, 2003;Wang et al 2006). Also, an avirulent strain of S. enterica serovar Typhimurium colonized carrots and radishes which were grown on a field treated with S. enterica serovar Typhimurium-contaminated composted manure or irrigation water (Islam et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, the route of contamination remains vague. It was shown that S. enterica can contaminate entire tomato plants following direct root inoculations in a hydroponic system , and S. enterica was observed to contaminate tomato fruits by direct inoculation of flowers (Guo et al, 2001). These results suggest that Salmonella contamination of tomatoes can occur during cultivation.…”
Section: Preparation Of S Enteritidis-egfp-contaminated Soilmentioning
confidence: 69%
“…Guo et al (2001) reported that brushing tomato flowers with a fivestrain cocktail of S. enterica (serovar Enteritidis, Harford, Michigan, Montevideo, and Poona) resulted in contamination of 25% of ripe fruits. The present result, however, showed that S. Enteritidis counts were below the detection limit (< 0.3 MPN/g) in the edible parts of tomato and calyces (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Since the most predominant place for harboring Salmonella in or on tomatoes has been found to be the outer surface (82%) [12], the ME biosensor method has been applied directly to the tomato surfaces without any further sample preparation. S. typhimurium was inoculated and grown directly on the tomato surfaces in order to compare the ME biosensor method with Q-PCR.…”
Section: Observation and Enumeration Of S Typhimurium Directly Grownmentioning
confidence: 99%